ENHANCING PVT SYSTEM PERFORMANCE WITH HYBRID Grp/Al₂O₃ NANOPARTICLES - Zaid. A. Shaalan; Adnan. M. Hussein; M. Z. Abdullah (Journal of Mechanics of Continua and Mathematical Sciences)
The enhancement effect of hybrid nanofluids, especially with Grp/AL2O3 nanoparticles could be considered promising in enhancing the cooling of photovoltaic (PV) panels. Scholars have established that these nanoparticles improve heat transfer and convective heat transfer, therefore increasing the efficiency of solar panels. This work employed CFD analysis to investigate the characteristics of a new hybrid nanofluid, which is (Graphene Nanoplatelets (Grp) and aluminum Oxide (AL2O3). The system used in this study comprises three solar panels with identical specifications but using different cooling methods: air-cooled, water-cooled, and hybrid nanofluidcooled. The found data demonstrates that the electrical efficiency of the solar cells, cooled by the hybrid nanofluid, is comparatively higher than the air-cooled and watercooled solar cells: 12.2% and 7.6%, respectively, and the rise in power of the solar cells cooled by the hybrid nanofluid is comparatively higher to the air-cooled and water-cooled solar cells: 12.72% and 6.87 When applying the hybrid nanofluid cooling technique, the maximum surface temperature of the PV cells was reduced by 114% than that in air-cooled cells and 1.9% from water-cooled cells. As for the practical applications, it can be noted that hybrid nanofluids have demonstrated rather promising effects, enhancing the cooling efficacy of photovoltaic panels and, therefore, the efficacy of both overall solar energy systems.